Implementation of Simple Additive Weights to Determine Priorities for The Resolution of Information Technology Problems - Rizky Panji Santoni; Jajat Sudrajat; Asep Ririh Riswaya (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
The Regional Secretariat of West Java Province (Setda Jabar) is a government agency within the local government environment in West Java Province. Along with the development of information technology, using technology such as computers and the internet in a government agency is very important to support work. There are times when devices and systems do not work correctly, such as internet disturbances and computer software and hardware problems handled by technicians. Technicians not only manage information technology infrastructure at the West Java Regional Secretariat but also manage information technology infrastructure in three (3) official houses. Technicians are also faced with an organizational structure with many bureaus and sections. There is yet to be a definite procedure in the complaint reporting process. There is no helpdesk system as a reporting medium. With the many bureaus, the number of information technology facilities served so that technicians find it difficult to determine the priority of the work that must be served first. Given these problems, a Decision Support System approach uses the Simple Additive Weight method by using determining criteria and weights. The criteria used include Work Units, Positions, Types of Complaints, and Official Notes. The system development method used is Object Oriented Analysis Design (OOAD). This system is expected to assist technicians in determining services that match their needs and situations.